2015
DOI: 10.1007/s10877-015-9709-4
|View full text |Cite
|
Sign up to set email alerts
|

Near-infrared spectroscopy determined cerebral oxygenation with eliminated skin blood flow in young males

Abstract: We estimated cerebral oxygenation during handgrip exercise and a cognitive task using an algorithm that eliminates the influence of skin blood flow (SkBF) on the near-infrared spectroscopy (NIRS) signal. The algorithm involves a subtraction method to develop a correction factor for each subject. For twelve male volunteers (age 21 ± 1 yrs) +80 mmHg pressure was applied over the left temporal artery for 30 s by a custom-made headband cuff to calculate an individual correction factor. From the NIRS-determined ips… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…; Hirasawa et al. , ). Muscle blood flow in humans may be evaluated using positron‐emission tomography or magnetic resonance imaging (Heinonen et al.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…; Hirasawa et al. , ). Muscle blood flow in humans may be evaluated using positron‐emission tomography or magnetic resonance imaging (Heinonen et al.…”
Section: Discussionmentioning
confidence: 98%
“…) albeit with a contribution of SkBF (Hirasawa et al. , ) and myoglobin (Madsen and Secher ). NIRS variables were only evaluated in seven subjects because for three subjects it was difficult to evaluate NIRS variables under water.…”
Section: Methodsmentioning
confidence: 99%
“…Recent research has indicated that changes in skin blood flow were highly positively related to changes in HBO and HBR levels (r = 0.737) (Hirasawa et al, 2015). To obtain an estimate of changes in skin blood flow, one study formulated a correction factor used in the MBLL formula that was derived for each individual by monitoring simultaneously changes in cerebral oxygenation levels and changes in skin blood flow (Hirasawa et al, 2016) and then applied the individual correction factor to the analysis of task performance changes. Future fNIRS studies with children with FASDs may benefit from using such a protocol to rule out any such biases that differential levels of skin blood flow may have in group comparison studies.…”
Section: Discussionmentioning
confidence: 99%
“…A degree of blood pressure autoregulation may occur, but much more weakly than in the cerebral vasculature (Wilson et al, 2005). Flow is not directly related to neural activity, although there may be indirect effects via the SNS, for example if the functional task is challenging or stressful (Kenney and Johnson, 1992, Hirasawa et al, 2015). A detailed model of scalp behaviour would need to account for many or all of these factors.…”
Section: Methodsmentioning
confidence: 99%